(untitled) (Dhaka University Journal of Biological Sciences, 2012)
An experiment was conducted to find out the responses of two varieties of rice to NAA on nitrogen (N), phosphorus (P), and potassium (K) uptake by straw and root at three different stages and NPK concentrations in grains. Nitrogen, P and K uptake by both straw and root were found to increase and decrease depending on the concentration of NAA and also on the stages of development. Uptake of NPK were recorded higher at the tillering stage and at harvest with a few exceptions, whereas, lower uptake at the flowering stage in most cases. However, NPK concentrations in grains were favourly influenced by 200 ppm NAA in both the varieties except K concentration of BRRI dhan?29 (V1). Variations among the treatments were non?significant in the majority of cases. Out of the two varieties BRRI dhan?29 (V1) showed comparatively more positive response to NAA that BRRI dhan?50 (V2). DOI: http://dx.doi.org/10.3329/dujbs.v21i1.9740 DUJBS 2012 21(1): 9-15